Research of the Influence of Different Methods of Bakery Properties of Flour According to the Results of Test Laboratory Baking (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Checking the technological analysis of wheat grain grown in the fields of the Syrdarya region.